Pengaruh Lingkungan Kerja Fisik Dan Komunikasi Terhadap Kinerja Pegawai Pada Dinas Kependudukan Dan Pencatatan Sipil (DISDUKCAPIL) Kota Tangerang Selatan - Nurmaulana Zulfi; Bambang Sutarto (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The purpose of this study is to determine the effect of Physical Work Environment and Communication on Employee Performance at the Department of Population and Civil Registration (DISDUKCAPIL) of South Tangerang City, both partially and simultaneously. The research method used is a quantitative approach with an associative research type. The results show that partially, the Physical Work Environment variable has a significant effect on Employee Performance with a significance value of 0.000 < 0.05 and a tcount value of 2.779 > ttable 1.987. The Communication variable also has a significant effect on Employee Performance with a significance value of 0.000 < 0.05 and a tcount value of 4.361 > ttable 1.987. Simultaneously, the F-test results indicate that the Physical Work Environment and Communication have a positive and significant effect on Employee Performance with a significance value of 0.000 < 0.05 and an Fcount value of 10.201 > Ftable 3.10. The Coefficient of Determination (Adjusted R Square) test shows a value of 0.190 or 19%, which means that simultaneously, the Physical Work Environment and Communication contribute 19% to Employee Performance, while the remaining 81% is influenced by other variables outside this research model.